Dinamika Penerimaan Diri (Self Acceptance) Pada Lansia Penderita Diabetes Mellitus Tipe II DI Posyandu Lansia Desa Tasikhargo Jatisrono Wonogiri Tahun 2015 - Hanna Hanindyastiti; Insiyah Insiyah ((JKG) Jurnal Keperawatan Global, 2017)
Abstract: Dynamics, Self-Acceptance, Elderly Patients, Diabetes Mellitus Type II. As getting older, an elderly suffered from many physical and mental consequences. The characteristics of geriatric syndrome most often experienced by diabetes mellitus depression, withdrawl and away from social activities. Some of them are suffering from severe and long diabetes mellitus. This research aims to describe how the dynamics of self-acceptance in elderly patients type II of Diabetes Mellitus in Posyandu Tasikhargo, Jatisrono, Wonogiri district in 2015.The research method used is qualitative method with the collection of data using in-depth interviews and Focus Group Discussion (FGD). The sample comprised 9 respondents with the inclusion criteria. According the results of the research on the results of the dynamics of self-acceptance to elderly patients with diabetes mellitus type 2, seven of the nine respondents able doing the good dynamics of research self. The good Self-acceptance backed by two. The inside factor including the state of his own altruistic, feeling confident, capable of receiving the advantages and the rest after suffering from diabetes mellitus. The outside factors are the environment and support social. The good dynamics of self- acceptance in elderly patients with type II of diabetes mellitus in posyandu Tasikhargo, Jatisrono, Wonogiri is by doing diabetes management, pray and genuinely accept the state of being experienced by patients. Social support and environmental influence self-acceptance. Lack of education is a factor make the difficult of self-acceptance, so the family support is actually useful to improve health. However, this support sometimes is perceived negatively by the patients as a restraint for themself, because they feel set up and was not released. For nurses with more emphasis on health education about diabetes mellitus that diabetics have sufficient knowledge of the conditions experienced.